Tendências de TCC entre formandos em ciências biológicas no IFAM - Nogueira, Anny Larisse de Oliveira (Brasil, 2022)
The work of conclusion of course (CBT) is a scientific activity of systematizing knowledge about an object of study or problem. This research presents the results of the mapping of monographs constructed next to the course of Biological Sciences Degree of the IFAM, from 2006 to 2012. The aim was to identify, based on this mapping, the research themes, methodological approaches, tools for collection of data and formative aspects that indicated allusions to the formation by competences and professor researcher. For that, a documentary research was carried out, which analyzed 85 monographs. The qualitative research approach was predominant with questionnaire use and directed interview, as well as emphasis on ecology, parasitology and botany. In the general topics related to education, the study prevailed with didactic resources, cross-cutting themes, teaching strategies and articulation of theory and practice in teaching. As for the formative aspects, two studies were registered that indicated the formation by competences and professor researcher. The study became relevant because it is necessary to observe if the one proposed in the PPC has been fulfilled, since the profile to be formed is the Professor Researcher of Biological Sciences.